Alterations in Bone Turnover during Chemotherapy in Children with Acute Lymphoblastic Leukemia - Gupta, Vineeta; Dash, Shalini; Aggarwal, Priyanka; Singh, Surya Kumar (South Asian Journal of Cancer, 2021)
Background Disturbances of bone metabolism frequently occur in children with acute lymphoblastic leukemia (ALL), leading to increased risk of osteopenia and osteoporosis at diagnosis, during and after completion of chemotherapy. The present study was performed to evaluate alteration in bone mineral metabolism in children with ALL during chemotherapy.Method Fifty newly diagnosed patients with ALL in the age group of 2 to 14 years were included. Relapsed and refractory cases were excluded. Enrolled children were stratified into standard and high risk according to National Cancer Institute criteria. Quantitative analysis of bone resorptive marker carboxyl-terminal telopeptide of human type 1 collagen (ICTP) was assessed at baseline and 3 months after chemotherapy by the sandwich enzyme-linked immunosorbent assay technique.Results Of 50 patients enrolled, 21 were standard and 29 were high risk. The mean age was 7.75 ± 4.0 years and the male-to-female ratio was 3.5:1. ICTP levels were analyzed in 44 patients, of which 37 (84%) showed significantly increased levels. The mean ICTP level in patients at diagnosis and controls was 1.78 ± 1.39 and 0.96 ± 0.32 µg/L, respectively (p = 0.001). The mean ICTP level at 3 months after chemotherapy increased to 3.55 ± 1.40 µg/L (p = 0.000). It was significantly increased in males (p = 0.000) and in B cell ALL group (p = 0.000) in comparison to females and T cell group. Both standard and high risk groups were equally affected (p = 0.000). On multivariate analysis, no single risk factor could be identified.Conclusion The marker of bone resorption (ICTP) in children with ALL was increased at diagnosis, which further increased during chemotherapy. The disease itself and the intensive chemotherapy both contributed to the increased levels.
Keywords: skeletal morbidity; acute lymphoblastic leukemia; bone metabolism; carboxyl-terminal telopeptide of human type 1 collagen (ICTP); quality of life